1996
DOI: 10.1111/j.1348-0421.1996.tb03309.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Teratogenicity of Aino Virus in Chick Embryos

Abstract: Aino virus (AIV; JaNAr 28 strain) 103 TCID50/0.2 ml was inoculated in the yolk sac of 8-day-old chick embryos. Recovery and titration of the virus from various organs including the central nervous system (CNS) and skeletal muscle were performed at 2, 4, 7, 10 and 13 days after inoculation (PI). AIV was systemically disseminated and proliferated even 2 days PI. The titers of the recovered virus from the CNS and from skeletal muscle was the highest at 4 days PI and declined with time, whereas hydranencephaly, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Although serologic data suggested that AINOV caused congenital abnormalities of cattle and sheep in Japan and Australia [1,12], the pathogenicity of AINOV in cattle has not been demonstrated. Viral teratogenicity in cattle and sheep has been well demonstrated for AKAV [2,8,11,13], a member of bunyavirus; however, the teratogenicity of AINOV has been examined only in chick embryos [5][6][7]. To determine the role of AINOV in inducing congenital malformation, fetal cattle were exposed to maternal and direct routes of infection with the virus and examined for transplacental activity of the virus and developmental abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although serologic data suggested that AINOV caused congenital abnormalities of cattle and sheep in Japan and Australia [1,12], the pathogenicity of AINOV in cattle has not been demonstrated. Viral teratogenicity in cattle and sheep has been well demonstrated for AKAV [2,8,11,13], a member of bunyavirus; however, the teratogenicity of AINOV has been examined only in chick embryos [5][6][7]. To determine the role of AINOV in inducing congenital malformation, fetal cattle were exposed to maternal and direct routes of infection with the virus and examined for transplacental activity of the virus and developmental abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study revealed that AINOV was equally teratogenic for cattle as AKAV. It has been shown that chick embryos manifest marked hydranencephaly, cerebellar hypoplasia, arthrogryposis and scoliosis by inoculation into the yolk sac of eight days embryo with AINOV [5][6][7]. Kitano et al [6] mentioned that cerebellar hypoplasia in AINOV-infected chick embryos constitutes a distinctive difference from AKAV-infected chick embryos, which showed hydranencephaly and myopathy [9].…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest that the Aino virus may be involved in the etiology of hydranencephaly, arthrogryposis, and cerebellar hypoplasia in cattle. In fact, studies have shown that chick embryos infected with the Aino virus went on to develop arthrogryposis, hydranencephaly, and cerebellar hypoplasia (12,13,14). However, in order to develop a vaccine or other preventive measures against this virus, further information on its antigenic diversity within the epidemic area will be needed.…”
mentioning
confidence: 99%